2015
DOI: 10.1016/j.bbalip.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The active site of yeast phosphatidylinositol synthase Pis1 is facing the cytosol

Abstract: Five yeast enzymes synthesizing various glycerophospholipids belong to the CDP-alcohol phosphatidyltransferase (CAPT) superfamily. They only share the so-called CAPT motif, which forms the active site of all these enzymes. Bioinformatic tools predict the CAPT motif of phosphatidylinositol synthase Pis1 as either ER luminal or cytosolic. To investigate the membrane topology of Pis1, unique cysteine residues were introduced into either native or a Cys-free form of Pis1 and their accessibility to the small, membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…PLC makes DAG and this undergoes five modifications to be returned to PI(4,5)P2 (Figure 1). But the second and third of these modifications are carried out by ER membrane enzymes [12,13], the active sites of which are located in short (≤20 aa) loops on their cytosolic faces. Therefore, plasma membrane lipids ≥15 nm away [14•] cannot be substrates.…”
Section: Ca 2+ Signaling At the Plasma Membrane And The Phosphatidylimentioning
confidence: 99%
“…PLC makes DAG and this undergoes five modifications to be returned to PI(4,5)P2 (Figure 1). But the second and third of these modifications are carried out by ER membrane enzymes [12,13], the active sites of which are located in short (≤20 aa) loops on their cytosolic faces. Therefore, plasma membrane lipids ≥15 nm away [14•] cannot be substrates.…”
Section: Ca 2+ Signaling At the Plasma Membrane And The Phosphatidylimentioning
confidence: 99%
“…PI is synthesized on the cytosolic face of the ER (Bochud and Conzelmann, 2015), from where some is “flopped” to the luminal leaflet for the synthesis of glycosylphosphatidylinositol-linked proteins (Vishwakarma et al, 2005). The remaining PI has been shown to be distributed fairly evenly across most organelle membranes by sub-cellular fractionation (Vance, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Early subcellular fractionation and reconstitution experiments suggested that the active site of Pis1 may face the cytosol [64,82]. Very recently, by introducing cysteine residues at various positions in the primary sequence of S. cerevisiae Pis1 and monitoring their accessibility to alkylating reagents, the cytosolic location of the active site was confirmed [83] (Figure 7). In addition, an active site facing the cytosol is in line with modeling studies of Pis1 based on the crystal structures of A. fulgidus CDP-alcohol-phosphotransferases (see above) [83,84].…”
Section: Subcellular Location and Membrane Topology Of Phosphatidylinmentioning
confidence: 99%
“…Very recently, by introducing cysteine residues at various positions in the primary sequence of S. cerevisiae Pis1 and monitoring their accessibility to alkylating reagents, the cytosolic location of the active site was confirmed [83] (Figure 7). In addition, an active site facing the cytosol is in line with modeling studies of Pis1 based on the crystal structures of A. fulgidus CDP-alcohol-phosphotransferases (see above) [83,84]. In mammalian cells, PI synthase was originally found in a mitochondrial fraction from kidney cells [85] and the ER in rat lung pneumocytes [86,87].…”
Section: Subcellular Location and Membrane Topology Of Phosphatidylinmentioning
confidence: 99%
See 1 more Smart Citation